Adopting Technological Methods in the Algerian Higher Education: Challenges and Recommendations - Dou, Abdelbasset (La Nouvelle Publication Universitaire (NPU), 2021)
This work attempts to discuss the challenges that the Algerian educational system encounters while keeping pace with the modern approaches of teaching. It further provides some recommendations to teachers, learners, educators and policymakers. In order to spotlight the major obstacles in the road of technology-assisted courses, the researcher has used the interview as a tool of investigation with ten teachers from Mostaganem university. In addition, the interview aims at reflecting on teachers’ opinions and beliefs through sharing some implications and offering relevant recommendations. The findings have shown that there are two major sources of challenges facing the implementation of technology: the syllabus quality and quantity, and the imbalance of practical and theoretical sides of tutoring. Despite the economic factor, some technological techniques that go through simple stages of preparation, presentation, follow-up and finally evaluation are inexpensive and could not be reflecting the information divide effect.
Keywords: The Algerian higher education, technological methods, challenges, recommendations.